Taking off after new applications. (Manufacturing Engineering)
Waterjet cutting is no longer a mystery. Even materials used in sensitive applications can be cut without heat affected zones and heat deformation. Complex 3-D shapes also can be machined through the use of sophisticated programming and 3-D machining heads